Os reflexos da aplicação do planejamento interdisciplinar no ensino de ciências no 1º ciclo de alfabetização - Carlesso, Janaína Pereira Pretto (2015)
The aim of this study was to investigate the contributions of application planning with Science subjects in an interdisciplinary format of practice from teacher to student performance. The sample consisted of two groups - two groups of literacy cycle -1st the 3rd year of primary school - the same school: a group in which interdisciplinary activities were carried out with thematic Sciences (group interventions - GCI) and a group followed with the independent disciplinary planning, (group without intervention - GSI). For two years a multidisciplinary team collaborated with the formation of a public school teacher in the organization, planning and implementation in the classroom, activities involving science thematic integrated the contents of Mathematics and Portuguese. The interdisciplinary design was applied by the same teacher in class for two consecutive years with the same group of students. To identify the effects of the interdisciplinary, it was conducted to evaluate the performance of students in both groups. Through a comparative analysis between the groups was investigated how the interdisciplinary activities worked in the classroom contributed - not in isolation - in the performance of participating students in the group with interventions. To detect the contributions of this work in the practice of teaching, interviews were conducted. For the group without intervention, the number of correct answers in the tests did not show a significant correlation between the three areas assessed. In the group with interdisciplinary interventions, hit numbers in three tests correlated. The survey analysis pointed out that the group in which there was the inclusion of science teaching in the school planning activities in the early years of elementary school, through the application of an interdisciplinary approach, presented a significantly better performance in tests, not only in Science but also in mathematics and Portuguese. The developed interdisciplinary approach also promoted important benefits for the teaching of objective and subjective order, favoring reflection, integration of different disciplines, the construction and improvement of practice within the classroom.